Editorial - Sotang Public Campus (Sotang, Yearly Peer Reviewed Journal, 2025)
It is our great pleasure that we have come to you with one more issue of its Yearly Peer Reviewed Journal 'Sotang'. As it is the publication of Sotang Public Campus, Sotang, Solukhumbu, Nepal, the campus feels extreemly proud of its faculty members the other faculties from outside for their grat contribution with their resercch works. Teachers with their research articles have proved themselves that they not only impart or disseminate the subject matters included in the course books but also carryout scholarly research that help in the production of knowledge on their own. However making research and finding out something newer than that of the existing knowledge is not an easy task; it needs a great devotion, intensive study of related literature and a great deal of time and our faculty members, the real gems of Sotang Public Campus and all the other guest scholars have done it to bring the dream of the campus of continue its publication true. This journal is a spectrum of various research works that includes a variety of research articles from different fields of disciplines such as literature, language, pedagogy, management, health, publication etc. The combined feature of them have made the journal a really interdisciplinary, a Sotang covering a wider range of knowledge of various fields have made it true to its name due to its nature, words and spirit. We hope such diversity of knowledge will certainly provide different tastes to the readers of it. The editorial board finally expresses its gratitude to all respected professors who reviewed all researchable articles and contributed to this journal with their research works without which the publication of this would not be possible. Beside these all the other helping hands that include the other faculty members of the campus, campus administration, campus management committee all deserve our sincere thanks for their timely cooperation, and contribution. We hope even in the days to come, such cooperation, contribution and dedication from all will be available for the continuity of this publication.